Better Call Lucas: A Conversational Assistant for Older Adult Support - Dalmazo, Luan Matheus Trindade; Duarte, Luize; Pintarelli, Vitor Last; Todt, Eduardo (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2025: Anais da XXXV Brazilian Conference on Intelligent Systems, 2025)
This work presents the development of Lucas, a virtual assistant built entirely with open-source tools to support older adults in their daily routines. Built upon the Robot Operating System (ROS 2), the system is composed of modular nodes for wake word detection, speech processing, and natural language interaction. The assistant is triggered by the spoken expression “Opa Lucas” after which it records the user’s voice, transcribes the audio to text using Whisper, and processes the instruction using the LLaMA 3 Large Language Model. Depending on the user’s request, the system may access external tools, such as reminders and weather forecasts, via predefined APIs and SQL queries. The entire interaction is presented through a multimodal interface built with Pygame, combining speech synthesis and animated feedback. The assistant supports speaker identification through voice verification. To evaluate the assistant, a set of instructions was proposed to assess the accuracy, errors made, and the nature of the responses, including aspects such as harmfulness, helpfulness, and coherence. Additionally, the assistant was reviewed and tested by a geriatric care professional. The results demonstrate the assistant’s potential to deliver coherent, accurate, and timely instructions, suggesting its applicability in daily routines. The assistant’s source code is publicly available in a GitHub repository, along with documentation for setup and usage.